Dissection of Targeting Molecular Mechanisms of Celastrol-induced Nephrotoxicity via A Combined Deconvolution Strategy of Chemoproteomics and Metabolomics - Liu, Xueying; Zhang, Qian; Wang, Peili; Peng, Xin; An, Yehai; Chen, Junhui; Huang, Jingnan; Qin, Shuanglin; He, Hengkai; Hao, Mingjing; Tian, Jiahang; Yi, Letai; et al. (International journal of biological sciences, 2024)
Celastrol (Cel), derived from the traditional herb fordii Hook. f., has anti-inflammatory, anti-tumor, and immunoregulatory activities. Renal dysfunction, including acute renal failure, has been reported in patients following the administration of Cel-relative medications. However, the functional mechanism of nephrotoxicity caused by Cel is unknown. This study featured combined use of activity-based protein profiling and metabolomics analysis to distinguish the targets of the nephrotoxic effects of Cel. Results suggest that Cel may bind directly to several critical enzymes participating in metabolism and mitochondrial functions. These enzymes include voltage-dependent anion-selective channel protein 1 (essential for maintaining mitochondrial configurational and functional stability), pyruvate carboxylase (involved in sugar isomerization and the tricarboxylic acid cycle), fatty acid synthase (related to β-oxidation of fatty acids), and pyruvate kinase M2 (associated with aerobic respiration). Proteomics and metabolomics analysis confirmed that Cel-targeted proteins disrupt some metabolic biosynthetic processes and promote mitochondrial dysfunction. Ultimately, Cel aggravated kidney cell apoptosis. These cumulative results deliver an insight into the potential mechanisms of Cel-caused nephrotoxicity. They may also facilitate development of antagonistic drugs to mitigate the harmful effects of Cel on the kidneys and improve its clinical applications.